1970
DOI: 10.1113/jphysiol.1970.sp009203
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and subcellular localization of acetylcholine in the posterior pituitary of the rabbit

Abstract: SUMMARY1. Acetylcholine and neurohypophysial hormones were measured in subcellular fractions of rabbit neurohypophysis.2. Differential anddensity gradient centrifugation, followed by bio-assay and electron microscopy were used to separate and characterize the subcellular particles, or isolated nerve endings.3. Acetylcholine in the rabbit neurohypophysis was found to occur in small vesicles of about 40 nm diameter which had similar characteristics to the synaptic vesicles from central nervous tissue.4. Examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1971
1971
1985
1985

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…These receptors, when activated, could facilitate VP release by in creasing the amount of calcium which enters the terminals in response to an action potential. The report that acetyl choline is primarily found in non-neurosecretory nerve terminals in the pituitary [20] is consistent with this hypo thesis, and axo-axonic synapses have been reported in neu rohypophysis [2]. Alternatively, acetylcholine could act presynaptically to inhibit release of an inhibitory substance such as dopamine.…”
Section: Discussionsupporting
confidence: 59%
“…These receptors, when activated, could facilitate VP release by in creasing the amount of calcium which enters the terminals in response to an action potential. The report that acetyl choline is primarily found in non-neurosecretory nerve terminals in the pituitary [20] is consistent with this hypo thesis, and axo-axonic synapses have been reported in neu rohypophysis [2]. Alternatively, acetylcholine could act presynaptically to inhibit release of an inhibitory substance such as dopamine.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, acetylcholine (ACh) has been reported in the neuro hypophysis of rabbits, oxen and rats [19], where it appears by subcellular fractionation to be localized to vesicles of nerve terminals [20]. Acetylcholinesterase (AChE) has been found similarly in glands of cats [17], rabbits [19], and cattle [18], where it appears histochemically to be localized to pars intermedia parenchymal cells in the rat and in addition in certain pituicytes of the posterior pituitary in cat and rabbit [36, 37], Another group [7] additionally found AChE reac tion product over some nerve terminals in pars intermedia.…”
Section: Abstract the Characteristics Of Atropine-sensitive Binding mentioning
confidence: 99%
“…Lederis & Livingston (1970) found that isolated neurohypophysial nerve-endings could be obtained at the same density of sucrose as isolated elementary granules, and to attempt to study the functional aspects of uptake or metabolism of a particle without establishing whether it was enclosed in a cell membrane could lead to erroneous conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…They measured vasopressin and protein in this fraction and found that the hormone activity was low, but they did not measure acetylcholine in the gradient fractions. Lederis & Livingston (1968 examined small vesicles prepared from rabbit neurohypophysis in a way similar to that described by Bindler et al (1967), namely osmotic disruption of a preparation of neurosecretory nerve-endings followed by density gradient centrifugation, and found that 63 % of the acetylcholine in the gradient was localized in the small-vesicle fraction whilst the pituitary hormones were divided between the supernatant (36%) and elementary-granule fractions (36 %). Electron microscopy of these fractions confirmed that the acetylcholine-rich fraction consisted of small vesicles of 20-70 nm diameter and that the hormone-rich particulate fraction consisted mainly of elementary granules and occasional mito¬ chondria.…”
Section: Small Vesiclesmentioning
confidence: 97%